Contemporary Ijtihad on Biometric Data Protection in the Perspective of Maqashid al-Syariah - Syifa Fedira Az Zahra; Zakiyudin Fikri; Afif Nidhomul Ilmi; Friska Ayudia Ariani; Muhammad Rizal Firdaus (Kartika: Jurnal Studi Keislaman, 2026)
The rapid development of biometric technology carries a high risk to privacy due to the unique and permanent nature of such data. The recurring phenomenon of biometric data breaches in Indonesia indicates significant gaps in the existing data protection system. This research aims to analyze the legal formulation of biometric data protection through contemporary ijtihad and to examine the relevance of the Maqashid Sharia approach in providing protection within the digital era. The research method employed is normative legal research using a statute approach and a conceptual approach. The results indicate that under positive law, biometric data is classified as specific personal data based on Law Number 27 of 2022 concerning Personal Data Protection. From the perspective of Islamic law, contemporary ijtihad based on Maqashid Sharia views the protection of biometric data as an effort to achieve welfare through five essential elements (al-daruriyyat al-khamsah): the protection of life (hifz al-nafs), intellect (hifz al-’aql), property (hifz al-mal), lineage (hifz al-nasl), and honor and privacy (hifz al-’irdh). This approach serves as an ethical-moral foundation that complements the positive legal framework in addressing the rapid dynamics of digital technology